Peningkatan Pendapatan Keluarga Melalui Pengelolaan Sampah Rumah Tangga di Desa Penembang, Bengkulu Tengah - Oktridarti, Levy; Yori Manis Tika; Linda Astuti; Heni Indriani; Hania Sumarni; Seftya Dwi Sinta; Imron Rosyadi (Bengkulu Institute, 2024)
Household economic empowerment is one of the government's efforts to improve the welfare of the community. In its implementation, this effort is carried out by utilizing natural resources and potentials that exist in the environment around the house where the community itself lives. For the community in Penembang Village, Bengkulu Tengah Regency, household waste has not been utilized optimally, this is due to the lack of knowledge about the management and utilization of household waste. One way that can be done as a solution to this problem is to conduct counseling and training on household waste management to the community in Penembang village. In the counseling, household waste processing practices are also carried out, especially organic waste.